Environmental LCA of innovative reuse of all End-of-life tyre components in concrete - Maxineasa, Sebastian George; Neocleous, Kyriacos; Dumitrescu, Laura; Themistocleous, Kyriacos; Taranu, Nicolae; Hadjimitsis, Diofantos G. (My University, 2017)
This paper presents the environmental life-cycle assessment of concrete mixtures containing materials recycled from End-of-Life tyres, i.e. rubber particles, sorted steel wires and polymer/textile cord fibres. This life-cycle assessment is based on ILCD and the ISO standards and considers “cradle to gate”, i.e. from extraction of raw materials, tyre-recycling and up to concrete production in ready mixture concrete plants. In total, 21 different concrete mixtures were analysed, including rubberised concrete and fibre reinforced concrete; mixtures with hybrid fibres were also considered (i.e. reinforced with both recycled and manufactured fibres). The results of this LCA show that, for a functional unit of 1 m3 of concrete, cement is the main parameter contributing to the inventory of the examined concrete mixtures; this indicates the need of utilising “low energy” and low calcination cements to minimise their environmental impact. When performance-based functional units are considered in the LCA, the results highlight the importance of using these recycled materials in structural concrete applications that fully utilise the specific mechanical characteristics of each material, as demonstrated for rubberised concrete and steel fibre-reinforced concrete mixtures.
Keywords: Recycled steel fibres; Recycled textile fibres; End-of-Life tyres; Concrete; Recycled rubber